The Role of Endothelial Nitrit Oxide in Preeclampsia Onset - Ramya Sausan; Yusrawati, Yusrawati; Karmia, Hudila Rifa (Fakultas Kedokteran Universitas Andalas, 2025)
Background: Preeclampsia is a pregnancy-specific hypertensive disorder associated with significant maternal and fetal morbidity and mortality. Endothelial dysfunction plays a critical role in the pathogenesis of preeclampsia, with nitric oxide (NO) being a key regulator of vascular tone and endothelial function. This study aims to investigate the relationship between endothelial nitric oxide (eNOS) levels and the onset of preeclampsia. Methods: A cross-sectional study was conducted on pregnant women diagnosed with severe preeclampsia and receive treatment at Dr. M. Djamil Hospital, Padang. After met the inclusion criteria and do not have exclusion criteria, demographic and clinical data was taken. Maternal plasma concentrations of eNOS were determined by ELISA. Non-parametric statistics were used for analysis. Results: The study evaluated the levels of endothelial nitric oxide synthase (eNOS) in two groups of preeclampsia patients: those with Early Onset Preeclampsia (EOP) and Late Onset Preeclampsia (LOPE). The median eNOS levels were 50.43 pg/ml for the EOP group (range: 28.72 - 232.78 pg/ml) and 54.76 pg/ml for the LOPE group (range: 15.39 - 235.70 pg/ml). A Mann-Whitney U test revealed a p-value of 0.303, indicating no statistically significant difference in eNOS levels between the two groups. This suggests that the timing of preeclampsia onset does not significantly influence eNOS levels, providing insights into the disease's mechanisms. Conclusion: eNOS levels in the early preeclampsia (EOP) group were found to be lower compared to the late preeclampsia (LOPE) group. Although there was a difference in eNOS levels between the two groups, the difference was not statistically significant. Keywords: Preeclampsia, endothelial dysfunction, nitric oxide; pregnancy, hypertensive disorders